EVALUASI PROSES PEMBELAJARAN DENGAN JENIS DISCOVERY BASED LEARNING PADA MATA KULIAH KAJIAN MUSIK 2 DI PS. SENI MUSIK FBS UHN MEDAN - Ance Panggabean (Visi Sosial Humaniora, 2020)
Music Study Course 2 (Two) is one of the subjects with the main competence in interest / concentration in Musicology and History. The problem in this research is how the influence of the application of discovery based learning models in music study subjects and how the results of student creativity after using discovery based learning learning models. Through this discovery learning model learning is one of the teaching models where the lecturer does not directly give the final results or conclusions from the material he delivered, but students are given the opportunity to find and find that creativity, so that this learning process will be remembered by students of all time and the results obtained is not easily forgotten.